THE EFFECT OF ADDING PREMIX AQUAVITA BOSTER IN DIFFERENT DOSAGE WITH DIFFERENT TOWARDS GROWTH AND GRADUATION OF BAUNG FISH (Hemibagrus nemurus) - Lubis, Damayanti; M. tang, Usman; Pamukas, Niken Ayu (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACK This study aims to determine the best dose of aquavita premix booster in enhancing growth, feed efficiency and survival of baung fish. Research containers used in the form of aquariums measuring 60cm x 40cm x 40cm as many as 20 aquariums with a stocking density of 15 animals / aquarium. This study used aRandomized Design (CRD) consisting of five levels of treatmentand four replications. Each treatment was given the addition of aquavita premix of P0 (0 g / kg), P1 (1 g / kg), P2 (2 g / kg), P3 (2 g / kg), P4 (3 g / kg), and P5 (4 g / kg) feed. The results showed that the best treatment found in P4 (3 g / kg) of feed produced an absolute weight growth of 6.21 grams, absolute length of 4.26 cm, specific growth rate of 4.60%, feed efficiency of 114.47%, and survival of 96.66%. Key word : Boster Premix aquavita , Hemibagrus nemurus, growth.